Chemical disinfectants and antiseptics. Methods of airborne room disinfection by automated process. Determination of bactericidal, mycobactericidal, sporicidal, fungicidal, yeasticidal, virucidal and phagocidal activities. (8th April 2020) - British Standards Institution,
No abstract available